2009
DOI: 10.1002/chem.200802675
|View full text |Cite
|
Sign up to set email alerts
|

Chemo‐ and Regioselective Palladium‐Catalyzed Oxycyclization Reactions of Allendiols: Preparation of Five‐, Six‐, and Eight‐Membered Cycles

Abstract: Positive discrimination: Chemo- and regioselective palladium-catalyzed cycloetherification of allendiols, namely beta,gamma- and gamma,delta-allendiols, may occur by judicious choice of palladium-catalyzed conditions owing to their potential ability to discriminate between both nucleophilic sites (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 42 publications
0
11
0
1
Order By: Relevance
“…The asymmetric bromoetherification of 4 a could also be achieved to afford product 7 a in 64 % yield and 90 % ee with a Pd/Cu‐bimetallic catalytic system in the presence of lithium bromide. The ee value of 7 a was determined after debromination (Scheme ) 11. The absolute configuration of 3 was unequivocally determined by a single‐crystal X‐ray structural analysis of 7 a (Figure 1, also see the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…The asymmetric bromoetherification of 4 a could also be achieved to afford product 7 a in 64 % yield and 90 % ee with a Pd/Cu‐bimetallic catalytic system in the presence of lithium bromide. The ee value of 7 a was determined after debromination (Scheme ) 11. The absolute configuration of 3 was unequivocally determined by a single‐crystal X‐ray structural analysis of 7 a (Figure 1, also see the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Alcaide et al have demonstrated that b,g-and g,d-allendiols 210 undergo intramolecular cyclization to a variety of enantiopure oxacycles 211 or 212 of different ring sizes in the presence of LiBr (Scheme 58). [157] However, there are only a few examples of the catalytic enantioselective cyclic allylation by carbopalladation. In 1991,…”
Section: Cyclizations In the Presence Of Organic Halides Or Hxmentioning
confidence: 99%
“…Interestingly, trans ‐fused β‐lactam oxocines 92 were obtained in good yields in a totally chemo‐ and regioselective fashion using the PdCl 2 ‐catalyzed cyclizative coupling reaction with allyl halides ( Scheme ), through an 8‐ endo ‐ trig cyclization by attack of the primary hydroxy group to the terminal allene carbon atom. [43] Apparently, this is the first example of an 8‐ endo cyclization at the terminal allene carbon atom of a δ‐allenol. Chemical evidence of the presence of a new eight‐membered oxacycle fused to the β‐lactam ring was obtained by oxidation of adduct 92a (R 1 = 4‐MeOC 6 H 4 , R 2 = Me) with DessMartin periodinane to afford ketone 93 (Scheme ).…”
Section: Heterocyclizationsmentioning
confidence: 99%